Novel Ag@Nitrogen-doped Porous Carbon Composite with High Electrochemical Performance as Anode Materials for Lithium-ion Batteries - Chen, Yuqing (Nanomicro Lett, 2017)
A novel Ag@nitrogen-doped porous carbon (Ag-NPC) composite was synthesized via a facile hydrothermal method and applied as an anode material in lithium-ion batteries (LIBs). Using this method, Ag nanoparticles (Ag NPs) were embedded in NPC through thermal decomposition of AgNO(3) in the pores of NPC. The reversible capacity of Ag-NPC remained at 852 mAh g(−1) after 200 cycles at a current density of 0.1 A g(−1), showing its remarkable cycling stability. The enhancement of the electrochemical properties such as cycling performance, reversible capacity and rate performance of Ag-NPC compared to the NPC contributed to the synergistic effects between Ag NPs and NPC. [Image: see text]